Термодинамічні дослідження телуридів ербію методом ЕРС - Імамалієва, С. З.; Мехдієва, І. Ф.; Тагхієв, Д. Б.; Бабанли, М. Б. (Фізика і хімія твердого тіла, 2020)
The work presents the results of a thermodynamic study of the Er-Te system by the method of electromotive forces (EMF) in the temperature range of 300-450 K. From the EMF measurements of the concentration cells relative to the Er and ErTe electrodes, the partial thermodynamic functions of ErTe and Er in the alloys are determined, based on which the standard thermodynamic formation functions and the standard entropies of the intermediate compounds ErTe3, Er2Te3, and ErTe are calculated. A comparative analysis of the obtained data with the literature is carried out.